Role of sex and training characteristics on exercise effects on cardiovascular aging: protocol for a systematic review with meta-analysis of randomized trials - Ciolac, Emmanuel Gomes [UNESP]; Babjakova, Jana; de Abreu, Raphael Martins; Mao, Su-Jie; Qian, Guoping; Teixeira do Amaral, Vanessa [UNESP]; Wrzesinski, Bartlomiej; Ferron, Artur Junio Togneri [UNESP]; Ossowski, Zbigniew; Francisqueti-Ferron, Fabiane Valentini [UNESP]; Yeniğün, Seda Cansu; Fernandes, Bianca [UNESP]; et al. (Springer Nature, 2024)
Background: Cardiovascular diseases remain a leading global cause of mortality worldwide especially in older adults. Although it is known that regular exercise reduces cardiovascular diseases incidence, its effects on specific cardiovascular aging parameters considering the influence of sex and different exercise designs are still not fully understood. Therefore, this systematic review and meta-analysis aims to evaluate the effects of different physical exercise protocols on age-related cardiovascular outcomes in older adults. Methods: This systematic review and meta-analysis will be reported in agreement with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement. Articles will be eligible if they are randomized controlled trials with a primary objective of evaluating the chronic effects of exercise interventions on cardiovascular aging parameters. Search strategy will be performed from the inception to September 30th, 2023, in the following electronic databases: MEDLINE (Ovid), SCOPUS (Elsevier), Embase, Sport Discus (EBSCO), Cochrane Central Register of Controlled Trials (CENTRAL), and Web of Science Core Collection (Clarivate Analytics). Data will be extracted and managed through Research Electronic Data Capture (REDCap) software. The Tool for the assEssment of Study qualiTy and reporting in EXercise (TESTEX) will be used to assess the methodological quality of included studies. Additionally, the quality of the findings will be evaluated using the Grading of Recommendations Assessment, Development and Evaluation (GRADE) profiler. Meta-analysis based on the random-effects model will be performed (if deemed suitable, considering the methodological and clinical heterogeneity of the studies) to estimate the effects of exercise training on cardiovascular aging variables (i.e., cardiac output; arterial stiffness; stroke volume; endothelial function; and carotid intima-media thickness). Heterogeneity will be assessed with the I2 statistics, while the publication bias will be assessed based on Egger’s test. Discussion: To the best of our knowledge, this will be the first systematic review and meta-analysis to investigate the impact of sex and training protocols on the cardiovascular aging parameters. Moreover, the findings of this systematic review and meta-analysis will provide evidence for health professionals in the management of elderly patients in order to optimize the exercise prescription to face the cardiovascular alterations related to the aging process, considering the effects of different protocols according to sex. Systematic review registration: PROSPERO CRD42023441015.
Keywords: Cardiovascular system; Elderly; Health promotion; Physical activity